Pattern recognition receptors in Crustacea: immunological roles under environmental stress - Betancourt, Jesús Luis; Rodríguez-Ramos, Tania; Dixon, Brian (Frontiers in Immunology, 2024)
Innate immunity is the first line of defense against infections and the only known available strategy for invertebrates. Crustaceans, being mostly aquatic invertebrates, are constantly exposed to potential pathogens in the surrounding water. Their immune system abolishes most microbes that enter and are recognized as a threat. However, the stress produced by high population densities and abiotic changes, in aquaculture, disrupts the host-pathogen balance, leading to severe economic losses in this industry. Consequently, crustacean immunology has become a prime area of research where significant progress has been made. This review provides our current understanding of the key pattern recognition receptors in crustaceans, with special focus on Decapoda, and their roles in triggering an immune response. We discuss recent developments in the field of signal transduction pathways such as Toll-like receptors (TLRs) and the immune deficiency (IMD) pathway, and examine the role of antimicrobial peptides (AMPs) in pathogen defense. Additionally, we analyze how environmental stressors—such as temperature fluctuations, ammonia levels, and pollution—impact immune responses and increase susceptibility to diseases. Finally, we highlight future research directions, emphasizing the need to explore the interactions between environmental stressors and immune signaling pathways and to develop strategies to enhance immune responses in crustaceans within aquaculture settings. Altogether, these advancements deepen our understanding of pathogen recognition in invertebrates and the specific defense mechanisms employed by crustaceans, particularly in response to infections triggered by pathogens under abiotic stressors.